Importancia de las normas y seguridad industrial en Medellín (2016)
In history it has always highlighted the need to find ways to build confidence in organizations through rules and security departments to provide confidence to workers and improve the organizational climate in order to build confidence. With the industrial revolution, according to advances in industrialization and automation generating new production processes and new risk factors for workers, currently industrial safety has a broader view and more people know about it and protection methods that exist to prevent future catastrophes, achieving calling it by different names not to be known as an area clearly processes of an organization. Objective set out to analyze the behavior of industrial safety in Medellin's business management considering the manage that give fire inspectors to the rules and laws by which is regulated industrial safety. For the methodology was made an interview that conducted two inspectors Fire in prevention station Fire Medellin, the two inspectors were busy but their answers were accurate, each interview was done separately but the answers were very similar perhaps attributed to both have a similar average experience in the field of industrial safety. An analysis of both interviews were conducted which could be noted that the main causes of accidents have been oversights of workers and lack of maintenance by the establishments was conducted, then the results obtained from both interviews raised